(untitled) (Avocetta, 2023)
The present study shows the results of the long-term monitoring of the Peregrine Falcon Falco peregrinus nesting in the Furlo Gorge State Nature Reserve located in the Marches region (central Italy). Monitoring took place between 1997-2022, when a minimum of 1 and a maximum of 3 breeding pairs nested within the protected area. During the study period, we identified 11 nesting sites used by the Peregrine Falcons that were located on cliffs with ledges and small niches, placed at an average height of 416 m (±89 m) a.s.l. Over the study period, the breeding pairs laid a total of 69 eggs, with an annual mean of 2.34 per pair, raising a total of 61 chicks of which 57 fledged successfully. Breeding attempts always occurred in March (with a pronounced peak in the second week) and incubation period lasted on average 32±1.60 days. During the 23 years of monitoring, the productivity rate was of 1.32 (n fledglings/n pairs), with a chick mortality of only 2.44% and a fledging success of 2.47 (fledglings/pairs with juveniles). This study highlights the Furlo Gorge as the second most important monitored breeding area for the Peregrine Falcon in the Marches region being the first one the Regional Park Gola della Rossa e di Frasassi (AN).